2017
DOI: 10.18805/lr.v0i0.8395
|View full text |Cite
|
Sign up to set email alerts
|

Studies on genetic variability, character association and path analysis for yield and its contributing traits in chickpea [Cicer arietinum (L.)]

Abstract: Genetic parameters, variability, heritability and genetic advance were studied among 20 genotypes of chickpea during during rabi 2012-13. The characters, seed yield per plant and 100-seed weight had high values of GCV, heritability and GAM and were found to be under greater control of additive gene action. While the traits, primary branches per plant, number of seeds per pod and protein content with moderate to low heritability coupled with low genetic advance appear to be more affected by on non-additive gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 4 publications
5
9
0
Order By: Relevance
“…Plate 1: Root behavior of P-acquisition efficient chickpea genotypes grown in P sufficient and deficient condition. Screening for Phosphorus (P) Acquisition Efficient Genotypes and Identification of Sequence Variations among P-Efficient... association for number of pod plant -1 , plant biomass, 100 seed weight and harvest index were reported in earlier studies (Aarif et al 2013;Jagadish and Jayalakshmi 2015;Chopdar et al 2017).…”
Section: P-inefficient Chickpea Genotypesmentioning
confidence: 83%
“…Plate 1: Root behavior of P-acquisition efficient chickpea genotypes grown in P sufficient and deficient condition. Screening for Phosphorus (P) Acquisition Efficient Genotypes and Identification of Sequence Variations among P-Efficient... association for number of pod plant -1 , plant biomass, 100 seed weight and harvest index were reported in earlier studies (Aarif et al 2013;Jagadish and Jayalakshmi 2015;Chopdar et al 2017).…”
Section: P-inefficient Chickpea Genotypesmentioning
confidence: 83%
“…Chopdar et al [25] found the highest genotypic coefficients variations for seed yield and 100-seed weight and moderate coefficient of variation for harvest index, number of pods per plant and biomass per plant and plant height in chickpea. And also genotypic coefficients of variations were low for days to maturity, days to 50 per cent flowering, primary branches per plant and number of seeds per pod.…”
Section: Genetic Variation Heritability and Genetic Advance In Geneti...mentioning
confidence: 99%
“…Hussain et al [22] studied genetic variability and mode of inheritance in eight quantitative traits of chickpea and reported that high broad sense heritability for grain yield (96.40%), number of pods per plant (93.19%), 100-grain weight (89.67%), biological yield (83.83%) and plant height (78.83). According to Chopdar et al [25], 100-seed weight had the highest heritability followed by days to 50% flowering (85.31), seed yield per plant (84.29), days to maturity (78.39), biomass per plant (69.06), number of pods per plant (68.06) and harvest index (67.51) in chickpea.…”
Section: Genetic Variation Heritability and Genetic Advance In Geneti...mentioning
confidence: 99%
“…The presence of substantial genetic variations, positive and highly significant correlated characters can be exploited in breeding programmes for improvement of chickpea in the geographical region. Chopdar (2016) studied twenty genotypes of chickpea with three replications. In the present study seed yield per plant found to have highly significant positive correlation with primary branches per plant, number of pods per plant, harvest index, number of seeds per pod, biomass per plant and 100 seed weight respectively.…”
Section: Correlationsmentioning
confidence: 99%